Children’s Learning of Non-adjacent Dependencies Using a Web-Based Computer Game Setting - Marimon, Mireia; Hofmann, Andrea; Veríssimo, João; Männel, Claudia; Friederici, Angela D.; Höhle, Barbara; Wartenburger, Isabell (Frontiers in Psychology, 2021)
Infants show impressive speech decoding abilities and detect acoustic regularities that highlight the syntactic relations of a language, often coded via non-adjacent dependencies (NADs, e.g., is singing). It has been claimed that infants learn NADs implicitly and associatively through passive listening and that there is a shift from effortless associative learning to a more controlled learning of NADs after the age of 2 years, potentially driven by the maturation of the prefrontal cortex. To investigate if older children are able to learn NADs, Lammertink and colleagues recently developed a word-monitoring Serial Reaction Time task and could show that 6- to 11-year-old children learned the NADs, as their reaction times increased then they were presented with violated NADs. In the current study we adapted their experimental paradigm and tested NAD learning in a younger group of 52 children between the age of 4 to 8 years in a remote, web-based, game-like setting (whack-a-mole). Children were exposed to Italian phrases containing NADs and had to monitor the occurrence of a target syllable, which was the second element of the NAD. After exposure, children did a “Stem Completion” task in which they were presented with the first element of the NAD and had to choose the second element of the NAD to complete the stimuli. Our findings show that, despite a large variability in the data, children aged 4 to 8 years are sensitive to NADs; they show the expected differences in reaction times in the Serial Reaction Time task and could transfer the NAD-rule in the Stem Completion task. We discuss these results with respect to the development of NAD dependency learning in childhood and the practical impact and limitations of collecting these data in a web-based setting.